(untitled) ("Temas Sociais" Journal, 2023)
With the conception of the Welfare State in Portugal, although late compared to the other countries of the European Union, it was possible to agree to a series of measures that provided an aging process with the dignity that was once unthinkable. However, these measures cannot be watertight, and it is possible to verify the evolution of social policies over the years to allow for adaptation to the times and needs that arise. Alongside this evolution and these changes, we have been witnessing the adaptation by the Social Service to a new reality, arming itself with tools that accompany this evolution, and which are essential for the area of aging. Defying its own policies and measures, the social service stands out for its diagnostic capacity, allowing for an adequate intervention, seeking the most appropriate answers, respecting the elderly, the family, and the community itself.